Perceived Consequences of USMLE Step 1 Pass/Fail Scoring Change: Neurosurgery Program Director Survey. (16th November 2020) - Huq, Sakibul; Khalafallah, Adham M; Botros, David B.R; Jimenez, Adrian; Lam, Shravika; Huang, Judy; Mukherjee, Debraj
Abstract: INTRODUCTION: The United States Medical Licensing Exam Step 1 exam (Step 1) has historically been a foundational element of applying to neurosurgery residency. Following a national conversation, exam scoring was recently changed from a three-digit numeric score to pass/fail. METHODS: A 23-question survey was built in Qualtrics and electronically administered to all neurosurgery program directors (PDs, n = 119) and associate program directors (APDs, n = 26) in the United States. Questions assessed baseline Step 1 utility for each program, including predictive power on resident success; global perceptions about the scoring change; perceptions of "winners and losers" from the change; and advice for future neurosurgery applicants. RESULTS: Seventy-five (52%) responses were received from 59 PDs and 16 APDs. Fifty-eight (77%) respondents indicated that they always screen applicants by Step 1 score, and forty-eight (64%) strongly or somewhat agreed that Step 1 is a strong predictor of resident success in their programs. Fifty-nine (79%) respondents strongly or somewhat disagreed with the scoring change, and fifty-four (72%) strongly or somewhat disagreed that it would have a positive effect on neurosurgery. While opinions of "winners and losers" from the change were mixed, forty-three (57%) respondents thought that students from prestigious schools would benefit, while forty-five (60%) thought that students from less prestigious schools would suffer. Twenty-two (29%) respondents thought that international medical graduates would suffer. Thirty-five (47%) respondents suggested that Step 2 CK would become "the new Step 1" for their program, and fifty (67%) intend to advise future applicants to take Step 2 CK before submitting their applications. CONCLUSION: Diverse, strongly held opinions regarding the Step 1 scoring change exist within neurosurgery. While there are noteworthy proponents of the change, a majority of neurosurgery PDs/APDs were dissatisfied with it, uneasy about its potential downstream effects on resident success, and concerned about potentially negative consequences on the resident selection process. Many PDs/APDs anticipate Step 2 CK filling the current role of Step 1. There is significant uncertainty regarding the scoring change, and its ultimate impact on neurosurgery remains to be seen.